Pengaruh Pelayanan Customer Service Dalam Mengatasi Keluhan Nasabah Pada PT Bank Sulutgo Cabang - J. Habu, Azhar; Simon, Sumarni (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
This study aims to determine and test the Effect of Customer Service Services in Overcoming Customer Complaints of Customer Satisfaction in P. Sulutgo Bank Limboto Branch. This type of research is quantitative research. The population in this study is the customer at P. Sulutgo Bank Limboto Branch. The sample used in this study was 100 customers. The data used are primary data obtained through a questionnaire that is processed using the IBM SPSS 25 application. Data analysis method used is a simple regression analysis. The results of this study indicate that there is a positive and significant influence of Customer Service on Customer Satisfaction at PT. Bank Sulutgo Limboto Branch with a significance value of 0.040. the value of t count is greater than t table for customer service variables of 2,077> 1,660 and a significance value of 0.040. This significance value is still smaller than the alpha value (0.05) so that H_0 is rejected